Effectiveness and safety of LX1 cream in the clinical treatment of facial contusions - Hung, Bui Tien; Kien, Duong Trung; Tung, Bui Anh; Trang, Nguyen Tuyet (Tạp chí Nghiên cứu Y học, 2025)
This research was conducted to evaluate the effectiveness and safety of LX1 cream in the clinical treatment of facial contusions. The study was conducted on 66 patients diagnosed with facial contusions, divided into 2 groups: Control group with patients treated according to the anti-inflammatory, analgesic and anti-edema protocol currently used in the department. Study group with patients treated according to the anti-inflammatory, analgesic and anti-edema protocol currently used in the department combined with the application of LX1 cream. The results showed that the study group had better improvement in pain levels according to the VAS scale with p < 0.05. The scores to assess the level of bruising after treatment of the study group that had a better tendency than the control group. We haven’t found any side effects of LX1 cream in the treatment of facial contusions.